Efektivitas Konseling Kelompok Realita untuk Meningkatkan Regulasi Diri Santri - Muslimah Muslimah (Coution : journal of counseling and education, 2020)
This study aims to determine the self-regulation of students of tahfidz and examine the effectiveness of group counseling on the improvement of self-regulation of students of tahfidz at the Ali Maksum foundation in the Krapyak boarding school. This research is an experimental study, with the determination of research subjects using purposive sampling based on self-regulation scale scores with a low category of ten female students, divided into two groups, namely 5 (five) students as an experimental group and 5 (five) students as a group control. Data analysis using the Mann Whitney & Wilcoxon test. Data collection using Self Regulatory Scale, Observation, Questionnaire, and Interview. The results showed that self-regulation before being given treatment was seen from intra-personal namely students of Tahfidz had not been able to make planning goals, decreased motivation, lack of discipline, disturbed mood due to factors delaying work, feeling lazy, feeling bored and bored. Interpersonal self-regulation is that the students of Tahfidz have a good relationship with friends, family and teachers in the boarding school. The meta-personal self-regulation that is santri tahfidz is able to straighten the intention to memorize the Koran solely to worship God. The self-regulation of students of tahfidz after being given treatment has changed. This can be seen from the students of Tahfidz who are able to make planning goals, motivation is increasing, more focused in achieving goals, more disciplined in carrying out activities, and getting accustomed to the condition of the boarding school environment. Reality group counseling is effective for improving students' self-regulation tahfidz the Ali Maksum foundation of the Krapyak boarding school. This can be seen in the non-parametric statistical calculation output Wilcoxon test with Asymp Sig results (2-tailed) = 0.039 <0.05 and Z-2.060a, meaning that the self-regulation score has increased after being given treatment. Meanwhile in the control group there was no significant increase between pre-test and post-test scores in self-regulation. This can be seen in the out-put statistical calculations with the results of Asymp Sig. (2-tailed) = 0.853> 0.05. Keywords: Reality Group Counseling; Self Regulation ; Santri Tahfidz. Abstrak Penelitian ini bertujuan untuk mengetahui regulasi diri santri tahfidz dan menguji efektivitas konseling kelompok realita terhadap peningkatan regulasi diri santri tahfidz di yayasan Ali Maksum pondok pesantren Krapyak. Penelitian ini merupakan penelitian eksperimen, dengan penentuan subjek penelitian menggunakan purposive sampling berdasarkan skor skala regulasi diri dengan kategori rendah sejumlah sepuluh orang santri puteri, terbagi menjadi dua kelompok yaitu 5 (lima) orang santri sebagai kelompok eksperimen dan 5 (lima) orang santri sebagai kelompok kontrol. Analisis data menggunakan uji Mann Whitney & Wilcoxon. Pengumpulan data dengan menggunakan Skala Regulasi Diri, Observasi, Angket, dan Interview. Hasil penelitian menunjukkan regulasi diri sebelum diberikan treatment dilihat dari intra-personal yaitu santri tahfidz belum mampu membuat perencaanaan tujuan, motivasi menurun, kurang disiplin, suasana hati terganggu akibat faktor menunda-nunda pekerjaan, rasa malas, merasa jenuh dan bosan. Regulasi diri interpersonal yaitu para santri tahfidz ini mempunyai hubungan yang baik dengan teman, keluarga dan guru yang ada di pondok pesantren. Regulasi diri meta-personal yaitu santri tahfidz mampu meluruskan niat menghafal Al-Quran semata-mata untuk beribadah kepada Allah. Regulasi diri santri tahfidz setelah diberikan treatment mengalami perubahan. Hal ini bisa terlihat dari santri tahfidz yang mampu membuat perencanaan tujuan, motivasi semakin meningkat, lebih fokus dalam mencapai tujuan, lebih disiplin dalam menjalani kegiatan, dan mulai terbiasa dengan kondisi lingkungan pondok pesantren. Konseling kelompok realita efektif untuk meningkatkan regulasi diri santri tahfidz yayasan Ali Maksum pondok pesantren Krapyak. Hal tersebut dapat dilihat pada out-put perhitungan statistik nonparametrik uji Wilcoxon dengan hasil Asymp Sig.(2-tailed) = 0,039 < 0,05 dan Z -2.060a, artinya bahwa skor regulasi diri mengalami peningkatan setelah diberikan treatment. Sementara itu pada kelompok kontrol tidak ada peningkatan yang signifikan antara skor pre-test dan post-test dalam regulasi diri. Hal tersebut dapat dilihat pada out-put perhitungan statistik dengan hasil Asymp Sig.(2-tailed) = 0,853 > 0,05. Kata kunci: Konseling Kelompok Realita; Regulasi Diri; Santri Tahfidz.